Intervensi yang Tepat: Fungsi Pemerintah Menangani Kegagalan Pasar - Wahyu Muh Syata (Journal of Literature Review, 2026)
This research aims to analyze the economic function of government in addressing market failures and the challenges of its implementation amidst the dynamics of the modern economy. Theoretically, the price mechanism acts as a signal to coordinate supply and demand, but in practice, markets often fail to produce efficiency and fairness simultaneously. Market failures arise from externalities (e.g., pollution), limited provision of public goods, information asymmetry, and imperfect competition such as monopolies and cartels. This research uses a descriptive qualitative method thru literature review and document analysis of books, journals, and policy reports. The findings indicate that state intervention is necessary to maintain economic stability and protect vulnerable groups, especially when externalities, information asymmetry, the unavailability of public goods, and non-competitive market structures (cartels/monopolies) cause distortions. Effective policies must be able to align economic actors' incentives with social goals thru the internalization of social costs, for example, with taxes, technical standards, emission limits, permits, and clean technology incentives. The government also plays a role in providing basic services and public goods thru direct provision, public-private partnerships, or targeted subsidies, accompanied by enhanced transparency and public literacy to reduce information inequality. Conceptually, this intervention aligns with the allocation, distribution, and stabilization functions, which demand data-driven diagnosis and measurable, adaptive, and accountable policy governance.